DETERMINAN YANG MEMPENGARUHI PENGGUNAAN E-FILING MELALUI PEMAHAMAN INTERNET SEBAGAI VARIABEL PEMODERASI : DETERMINANTS THAT INFLUENCE THE USE OF E-FILING THROUGH INTERNET UNDERSTANDING AS A MODERATING VARIABLE - Nada Aristia Maharani; Achmad Badjuri (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2023)
The purpose of this research was to test and analyze the effect of perceived ease, perceived satisfaction, and perceived benefit on e-Filing use, as well as to determine the effect of internet understanding as a moderating variable that can affect perceived ease, satisfaction, and benefit on e-Filing use. Individual taxpayers registered at KPP Pratama West Semarang were used in this study, totaling 43,948 taxpayers. With a sample size of 100 respondents, the sampling approach employed was simple random sampling. MRA (moderated regression analysis) was employed as the analysis approach. The results explain that perceived ease has a positive effect on the use of e-Filing and perceived benefit has a positive effect on the use of e-Filing, while perceived satisfaction has no significant effect on the use of e-Filing. Meanwhile, internet understanding is able to moderate the effect of perceived ease and perceived benefit on e-Filing use, but internet understanding is not able to moderate the effect of perceived satisfaction on e-Filing use.